Mount Andrew iron deposit, Kasaan Peninsula, Prince of Wales Island, southeastern Alaska - Wright, Wilford S.; Tolonen, A. W.; United States. Bureau of Mines. ([Washington, D.C.] : U.S. Dept. of the Interior, Bureau of Mines, 1947)
"November 1947." Mode of access: Internet.